CHANGES OF FACTORS OF NON-SPECIFIC PROTECTION OF THE ORAL CAVITY IN CHILDREN WITH GINGIVITIS AGAINST THE BACKGROUND OF THE USE OF ESSENTIAL OILS AND BENTONITE CLAY - GALKINA, OLGA P.; TER-POGOSYAN, DAVID A.; ABLAEV, KEMRAN D.; ABLAEV, KEMAL D. (The Bulletin of Contemporary Clinical Medicine, 2021)
Introduction. The prevention and treatment of inflammatory periodontal disease in children remains a topical issue in dentistry. This is due to the increasing prevalence of this disease in the early age groups. Remission periods of diseases in children are short. Therefore, treatment and preventive measures of periodontal tissue diseases in this population should be primarily focused on the regulation of nonspecific protection system at the local level. The components of the system are secretory immunoglobulin A, lysozyme and modified albumin. Using means of natural origin as regulators will allow to optimize treatment regimens and reduce allergic reactions. Aim. The aim of the study was to study the effectiveness of the complex for applications to the gingiva, consisting of means of natural and mineral origin of the Crimean deposit, in the regulation of local oral immunity in children with chronic catarrhal gingivitis. Material and methods. Twenty-eight children aged 11–12 years with moderate chronic catarrhal gingivitis were examined. The control group consisted of 12 healthy children of the same age. We used applications of phytopreparations on the gingiva in the treatment of chronic catarrhal gingivitis daily for 20 minutes, No 10. Complex for applications was essential oils of peppermint, pine, fennel, eucalyptus (1:1:1:1) on the basis of bentonite clay (10:1). Clinical and laboratory parameters were determined in the dynamics. Statistical processing was performed using the standard method of variation statistics. Comparison of the mean indices was conducted using Student’s t-criterion. Differences were considered reliable at p<0,05. Results and discussion. The criterion for the effectiveness of treatment was the positive dynamics of paraclinical indices (p<0,001). Indicators of oral dysbiosis decreased and reached values of oral microbiocenosis of healthy children. The content of sIgA increased 1,8 times (p<0,001). The level of salivary lysozyme activity increased 1,7 times (p<0,001) and reached normal values. The concentration of modified albumin decreased 1,6-fold. Conclusion. Inclusion of applications of the combination of essential oils based on bentonite clay of the Crimean deposit into the plan of treatment of chronic catarrhal gingivitis in children contributes to a pronounced relief of the signs of inflammation in the gingiva. The proposed complex has a pathogenetic orientation in the treatment of chronic catarrhal gingivitis, which is confirmed by the pronounced dynamics of nonspecific immunity parameters.